Organic Matter Decomposition: A View on The Fate of Lignocellulosic Materials - Bhattacharya, Susinjan (Discoveries in Agriculture and Food Sciences, 2023)
Organic matter decomposition, a complex process with all the physico-chemical and biological factors leads to breakdown of organic residues. The prime role in this process is played by microorganisms with their enzymes. The process is beneficial not only to generate matters of soil fertility enhancement, but also it can lead to the products that can add value to soil. Slow and difficult matters to be decomposed like lingo-cellulosic materials can also be subjected to this decomposition process for the generation of not only new and beneficial microflora, but also products of value. The present work discusses here in brief the process of organic matter decomposition and its importance in rice straw breakdown and lignocellulosic material decomposition.